JIME - The Open Learning Initiative: Measuring the Effectiveness of the OLI Statistics Course in Accelerating Student Learning - Lovett, Marsha; Meyer, Oded; Thille, Candace (Journal of Interactive Media in Education, 2008)
The Open Learning Initiative (OLI) is an open educational resources project at Carnegie Mellon University that began in 2002 with a grant from The William and Flora Hewlett Foundation. OLI creates web-based courses that are designed so that students can learn effectively without an instructor. In addition, the courses are often used by instructors to support and complement face-to-face classroom instruction. Our evaluation efforts have investigated OLI courses’ effectiveness in both of these instructional modes – stand-alone and hybrid. This report documents several learning effectiveness studies that were focused on the OLI-Statistics course and conducted during Fall 2005, Spring 2006, and Spring 2007. During the Fall 2005 and Spring 2006 studies, we collected empirical data about the instructional effectiveness of the OLI-Statistics course in stand-alone mode, as compared to traditional instruction. In both of these studies, in-class exam scores showed no significant difference between students in the stand-alone OLI-Statistics course and students in the traditional instructor-led course. In contrast, during the Spring 2007 study, we explored an accelerated learning hypothesis, namely, that learners using the OLI course in hybrid mode will learn the same amount of material in a significantly shorter period of time with equal learning gains, as compared to students in traditional instruction. In this study, results showed that OLI-Statistics students learned a full semester’s worth of material in half as much time and performed as well or better than students learning from traditional instruction over a full semester. Editor: Stephen Godwin (Open University, UK). Reviewers: Tim de Jong (Open University, NL), Elia Tomadaki (Open University, UK), and Stephen Godwin (Open University, UK). Interactive elements: A demonstration of the StatTutor statistics tutorial is available for playback from http://jime.open.ac.uk/2008/14/stattutor_tour/ . The demonstration is in Flash format. http://jime.open.ac.uk/2008/14/stattutor_tour/
Number: 1 Publisher: Ubiquity Press shortDOI: 10/ghcsxd KerkoCite.ItemAlsoKnownAs: 10/ghcsxd 2405685:U4FGVWP3
Keywords: IDR; Mathematics Learning; case studies; design patterns; games; methodology; open learning; pattern languages

An Investigation of Provision of Quality Basic Education in Ghana: A Case Study of Selected Schools in the Central Region - Ampiah, Joseph (Journal of International Cooperation in Education, 2008)
KerkoCite.ItemAlsoKnownAs: 2405685:NDYK3WSP
Keywords: ⛔ No DOI found

An evaluation of the effectiveness of computer assisted learning strategy and expository method of teaching biology: a case study of lumen Christi international high school, Uromi, Nigeria - Imhanlahimi, E. O.; Imhanlahimi, R. E. (Journal of Social Sciences, 2008)
Publisher: Taylor & Francis KerkoCite.ItemAlsoKnownAs: 10.1080/09718923.2008.11892621 10/ggppsj 2339240:BM5PL29D 2405685:JYCRNIYS

Computer aided instruction for out-of-school children in India: An impact study in Andhra Pradesh - Karnati, Romilla (University of Pennsylvania, 2008)
India has the largest number of out-of-school children, the majority of whom are girls. Against this backdrop, the Bridges to the Future Initiative (BFI), a computer-aided instruction (CAI) intervention was launched in Andhra Pradesh to bring children back to school. The BFI used multimedia software to teach basic literacy and numeracy skills through interactive stories and activities, in the local language Telugu. The methodology employed in the study was a quasi experimental design on a sample of around 140 children (age range 7-19 years). The research study included BFI sites which offered two hours of CAI a day and comparison sites which provided five hours of teacher-based instruction (TBI) a day. According to several socio-economic indicators on the survey, the sample came from poor families with low literacy levels. Findings from the survey indicated that these out-of-school children had a positive attitude toward education and a favorable perception of educated people. A majority of the sample dropped out of school to assist with domestic tasks or family run businesses and did not earn wages. The impact analysis indicated that learning took place in both contexts and learners achieved similar learning gains between pretest and posttest. However, learners in the BFI intervention were learning at a faster pace per hour than learners in the comparison sites. Learners in the CAI intervention achieved similar gains as learners in the TBI intervention in one-third of the instruction time. As such, there is a strong case to be made for the BFI program being more efficient in raising levels of literacy and numeracy scores. Within the BFI intervention group, there was evidence to suggest that the number of days attended resulted in an increase in posttest scores, particularly in reading. Furthermore, older students in the BFI intervention had consistently shown higher gains in learning across reading, writing, math and information and communication technology (ICT) literacy domains. Finally, girls in the BFI sample outperformed the boys and the biggest difference in test scores was seen in Math. The impact of the BFI intervention could also be documented by the fact that approximately 45% of the BFI sample returned to school in the next academic year. In sum, this research was one of the first to explore the context of out-of-school children in poor communities and the use of CAI in Telugu (local language) to bring these learners back to school. The results support the use of ICT with marginalized sections of society in developing countries in order to improve literacy skills. The findings of this study have the potential to inform policy makers on educational and gender equity issues.
KerkoCite.ItemAlsoKnownAs: 2339240:JE6NXAA5 2405685:8XTQWYRM
Keywords: Bridges to the Future Initiative; Computer-aided instruction; Education; India; Information and communication technologies; Information and communication technology (ICT); Literacy; Out-of-school children; School dropouts

Using learning design as a framework for supporting the design and reuse of OER - Conole, Gráinne; Weller, Martin (Journal of Interactive Media in Education, 2008)
The paper will argue that adopting a learning design methodology may provide a vehicle for enabling better design and reuse of Open Educational Resources (OERs). It will describe a learning design methodology, which is being developed and implemented at the Open University in the UK. The aim is to develop a 'pick and mix' learning design toolbox of different resources and tools to help designers/teachers make informed decisions about creating new or adapting existing learning activities. The methodology is applicable for designers/teachers designing in a traditional context – such as creation of materials as part of a formal curriculum, but also has value for those wanting to create OERs or adapt and repurpose existing OERs. With the increasing range of OERs now available through initiatives as part of the Open Courseware movement, we believe that methodologies, such as the one we describe in this paper, which can help guide reuse and adaptation will become increasingly important and arguably are an important aspect of ensuring longer term sustainability and uptake of OERs. Our approach adopts an empirically based approach to understanding and representing the design process. This includes a range of evaluation studies (capturing of case studies, interviews with designers/teachers, in-depth course evaluation and focus groups/workshops), which are helping to develop our understanding of how designers/teachers go about creating new learning activities. Alongside this we are collating an extensive set of tools and resources to support the design process, as well as developing a new Learning Design tool that helps teachers articulate and represent their design ideas. The paper will describe how we have adapted a mind mapping and argumentation tool, Compendium, for this purpose and how it is being used to help designers and teachers create and share learning activities. It will consider how initial evaluation of the use of the tool for learning design has been positive; users report that the tool is easy to use and helps them organise and articulate their learning designs. Importantly the tool also enables them to share and discuss their thinking about the design process. However it is also clear that visualising the design process is only one aspect of design, which is complex and multi-faceted. Editors: Alexandra Okada (Open University, UK). Reviewers: Teresa Conolly (Open University, UK), Rose Luckin (Institute of Education, UK), and Alexandra Okada (Open University, UK)
shortDOI: 10/ghgn54 KerkoCite.ItemAlsoKnownAs: 10/ghgn54 2405685:PTSWVK6M
Keywords: IMS learning design; Learning Design; e-learning; mind mapping